TISSUE DOPPLER IMAGING OF LONGITUDINAL MOVEMENT OF A FIBROUS RING OF MITRAL VALVE DURING ISOVOLUMIC PERIODS IN LEFT VENTRICULAR HYPERTROPHY - B. Amarjagal; S. B. Tkachenko; N. A. Mazur; N. F. Beresten (Столичная издательская компания, 2015)
Aim. To study change of rate and duration indicators of longitudinal movement of a fibrous ring of mitral valve (MFR) during isovolumic contraction (IVC) and relaxation (IVR) in hypertensive patients with various degree of a left ventricular hypertrophy (LVH). Material and methods. 80 hypertensive patients with moderate LVH (n=40) and severe LVH (n=40) are examined. The control group was presented by 30 healthy volunteers. Transthoracic echocardiography and Tissue Doppler imaging has been performed with ultrasonic tomograph "HDI 5000" (Philips). Results. Increase in LVH (Smm) and Е/Еmm associates with reduction in systolic velocity of movement of medial MFR (Smm). There is direct relation with duration of IVC-negative and IVR-positive components and myocardium mass index. Maximal velocity of IVC-positive component increases and maximal velocity of IVR-negative component decreases when LVH is growing. Conclusion. Velocities curves of IVC and IVR were bi-phase both in healthy persons and in hypertensive patients with LVH. Velocity and duration of positive and negative components of IVC and IVR depended on LVH degree.